The Effect of Amount on Release of NH4 and NO3-N in the Soil at two Harvests of Nitrogen through five BGA Species and N-fertilizers in Rice Growing Plant (Bangladesh Journal of Scientific and Industrial Research, 2008)
Among all treatments pots without growing rice plants containing N. muscorum showed the highest amount of mineral-N and P. boryanum was the lowest. On the contrary, treatments with rice plants containing all BGA species the amounts of NH4-N and NO3-N remaining were more or less equal to the fertilizers treatments. Among BGA species and fertilizers the highest amount of NH4-N and NO3-N were found at the 90 mg N pot-1 with urea and ammonium sulphate and A. doliolum gave the highest amount in comparison to other four species.Key words: Mineral-N, Nitrification, Denitrificatoin, Bluegreen algae, Rice yield.DOI = 10.3329/bjsir.v43i3.1160Bangladesh J. Sci. Ind. Res. 43(3), 427-432, 2008